White Kupang Flour (Corbula faba hinds), Fish Meal and Coconut Oil Usage on the Broilers Carcass Percentage and Abdominal Fat - Virgy Dzakina Fahrezy; Mirni Lamid; Setiawan Koesdarto; Emy Koestanti Sabdoningrum; Widya Paramita Lokapirnasari; Sunaryo Hadi Warsito (Jurnal Agro Veteriner, 2023)
This study was conducted to determine the effect of using white mussel flour fish flour and coconut oil on carcass percentage and abdominal fat percentage in broilers. This study used a completely randomized design consist 4 treatments and 5 replications. The study used DOC ( Day Old Chick ) with the strain Lohman MB 202 Platinum for 20 animals . The treatment in this study was ration without using white mussel flour (P0), ration using 10% white mussel flour (P1), ration using 12.5% white mussel flour (P2), ration using 15% white mussel flour (P3). Variables observed were carcass percentage and abdominal fat percentage. Data were analyzed by Analysis of Variance (ANOVA) if there is a significant effect then proceed with Duncan's Multiple range test significance level of 5%. The results of the analysis showed that P3 showed a significant difference with the control treatment (P0) and treatment P1 (p<0.05). The best broiler carcass percentage was in treatment P3 (76.02%) and P2 (74.7%) while the lowest was in treatment P0 (71.20%). The results of Duncan's test on the percentage of abdominal fat showed that the control treatment (P0), treatment P1, treatment P2, and treatment P3 were not significantly different (p> 0.05).